SME Internal Capability and Competitive Advantage in an Emerging Market: Moderating Effects of Firm Age - Donard Games; Roliza Roliza (Management Institute Faculty of Economics Universitas Andalas, 2019)
This study aims to determine the effect of small business internal capabilities on competitive advantage in which firm age was expected to moderate the relationship between these two constructs. The present study also considers the context of Indonesia as an emerging market economy as an important characteristic that can provide some additional perspectives related to SME competitive advantage. Here competitive advantage come from the resource-based view theory which sees SME capabilities will shape their competitiveness. The present study uses quantitative approach, using SmartPLS, by surveying 52 food SMEs in Padang, West Sumatra, Indonesia. It was found that SME internal capability was positively and significantly related to competitive advantage. Additionally, firm age moderated the relationship between SME internal capability and competitive advantage in young SME group (SMEs with the firm age less than 5 years), while this was not the case for old SME group (SMEs with the age more than 5 years). In an emerging market such as Indonesia, this may represent the urgency to consistently strengthen SME internal capability.